2016
DOI: 10.3390/ijms17091481
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Hypertension Consistently Predict the Presence and Extent of Coronary Artery Calcification in Symptomatic Patients: A Systematic Review and Meta-Analysis

Abstract: Background: The relationship of conventional cardiovascular risk factors (age, gender, ethnicity, diabetes, dyslipidaemia, hypertension, obesity, exercise, and the number of risk factors) to coronary artery calcification (CAC) presence and extent has never before been assessed in a systematic review and meta-analysis. Methods: We included only English language studies that assessed at least three conventional risk factors apart from age, gender, and ethnicity, but excluded studies in which all patients had ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…Meanwhile, moderate and heavy smokers had significantly higher plaque density compared to light smokers which indicates the progression of arterial calcification. It suggested that smoking dose and duration have continuing effects rather than simply a triggering effect which may be subsided after applying appropriate control measures [34]. Further, we observed stronger associations between moderate to heavy smokers in terms of higher number of daily smoking behavior or longer use with TAC volume even after adjusting for lesion density, indicating that increased vascular volume per se may likely play as central key roles in this pathological process.…”
Section: Discussionmentioning
confidence: 65%
“…Meanwhile, moderate and heavy smokers had significantly higher plaque density compared to light smokers which indicates the progression of arterial calcification. It suggested that smoking dose and duration have continuing effects rather than simply a triggering effect which may be subsided after applying appropriate control measures [34]. Further, we observed stronger associations between moderate to heavy smokers in terms of higher number of daily smoking behavior or longer use with TAC volume even after adjusting for lesion density, indicating that increased vascular volume per se may likely play as central key roles in this pathological process.…”
Section: Discussionmentioning
confidence: 65%
“…As particularly small, superficial calcifications may have an impact on plaque vulnerability, the need for a more precise analysis, exploiting the superior resolution of OCT, has emerged recently. We and others have previously shown that patients with T2DM yield a more vulnerable phenotype of coronary plaques, which may contribute to the higher frequency of cardiovascular events in this population [ 6 , 30 , 31 ]. Part of this vulnerable phenotype may be reverted through statin use, as the OCT-FORMIDABLE register suggests [ 32 ], and this effect seems to be enhanced by an optimal glucose control in the diabetic population [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arterial hypertension and endothelial growth factor-linked polymorphisms are reported to contribute to vascular damage [33,34]. Nicoll et al studied 15,769 patients on the relationships between conventional CV risk factors (age, gender, ethnicity, DM, dyslipidemia, hypertension, obesity, exercise) and coronary artery calcification, and found that hypertension and diabetes have the strongest association with coronary artery calcification [35].…”
Section: Hypertensionmentioning
confidence: 99%